2017
DOI: 10.1111/anae.13934
|View full text |Cite
|
Sign up to set email alerts
|

A survey of UK peri‐operative medicine: pre‐operative care

Abstract: SummaryThe majority of UK hospitals now have a Local Lead for Peri-operative Medicine (n = 115). They were asked to take part in an online survey to identify provision and practice of pre-operative assessment and optimisation in the UK. We received 86 completed questionnaires (response rate 75%). Our results demonstrate strengths in provision of shared decision-making clinics. Fifty-seven (65%, 95%CI 55.8-75.4%) had clinics for high-risk surgical patients. However, 80 (93%, 70.2-87.2%) expressed a desire for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 13 publications
(11 reference statements)
0
28
0
Order By: Relevance
“…Reduced quality of life and independence, increased rates of readmission, reduced longer term survival and an increased health economic burden may all follow. Healthcare professionals working across peri-operative medicine should develop strategies to address this problem [18][19][20].…”
Section: Background To Pre-operative Exercise Trainingmentioning
confidence: 99%
“…Reduced quality of life and independence, increased rates of readmission, reduced longer term survival and an increased health economic burden may all follow. Healthcare professionals working across peri-operative medicine should develop strategies to address this problem [18][19][20].…”
Section: Background To Pre-operative Exercise Trainingmentioning
confidence: 99%
“…Hartford-Beynon and Allan sensibly suggest the possible use of ultrasound screen prompts in 'Stop before you block' (SBYB) protocols [1,2]. We hope that manufacturers of ultrasound machines will take this seriously and consider the simple redesign of their software to incorporate this SBYB screensaver as a default.…”
Section: Frozen Ultrasound Image As a Prompt For Stop Before You Blockmentioning
confidence: 99%
“…Cardiopulmonary exercise testing (CPET) is increasingly available in centres throughout the UK, with 60% of clinics using CPET for high-risk surgical patients within their pre-operative assessment service [2]. When we introduced CPET to the oesophagogastric group, we designed a pathway that included early involvement of the peri-operative anaesthetic consultant in the pre-operative assessment clinic before discussion of individuals at the oesophagogastric MDT meeting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bougeard et al. identified that many hospitals are currently screening high‐risk surgical patients to assess potential benefits from pre‐operative lifestyle interventions, in particular, weight control, increased physical activity and reduced alcohol intake . However, only 23% of survey respondents had access to some kind of interventional weight management pathway, 28% for physical inactivity, and 30% for reducing alcohol intake .…”
mentioning
confidence: 99%